KEKUATAN TAHANAN LATERAL SAMBUNGAN GESER GANDA PADA KOMPOSIT LVL KAYU SENGON DAN WPC JATI - dyah puji astuti; dwi sat agus yuwana; evi puspitasari (Universitas Tidar, 2021)
Wood utilization technology is needed to meet the increasing demand for wood. These technologies are such us LVL and WPC. To make this wood a structural material, size limitations are a problem in its application. To overcome size limitations, a connesction is required. The research was conducted to determine lateral resistance in composite LVL Sengon wood and WPC Teak wood. This research use a standart bolt connecting tool for composite of LVL Sengon wood and WPC Teak wood with a variations in the diameter of 6 mm, 8 mm, 10 mm, and 12 mm using a double shear methode. This research was conducted at the Universitas Tidar and testing using UTM at Universitas Negeri Yogyakarta. Based on the results of the research, it was found that the value of lateral resistance testing on composite LVL Sengon and Teak WPC using standard bolts with variations in diameter 6 mm, 8 mm, 10 mm, and 12 mm were 4150,37 N, 5761,74 N, 8258 ,37 N, and 12416,33 N. The greatest lateral resistance occurs when using bolts with a diameter of 12 mm. The melt mode that occurs in all specimens is the IIIs melt mode, namely the formation of two plastic hinges in the bolt connection and damage to the side wood.